Age and location influence the costs of compensatory and accelerated growth in a hibernating mammal. (6th April 2020) - Heissenberger, Sarah; de Pinho, Gabriela Medeiros; Martin, Julien G A; Blumstein, Daniel T
Abstract: The increase of structural growth rates to compensate for a poor initial body condition, defined as compensatory growth, may have physiological costs, but little is known about its effects on individual fitness in the wild. Yellow-bellied marmots ( Marmota flaviventer ) are obligate hibernators and depend on fat accumulation acquired during an approximately 4-month summer to survive overwinter. We investigated the costs of survival and longevity of rapid growth in a wild population of yellow-bellied marmots. We used trapping data collected from 2002 to 2014 to calculate individual relative seasonal growth and assess its effects on longevity and annual survival of juveniles, yearlings, and adults. Sites were distributed in two main areas, down-valley and up-valley; the latter has a higher elevation and is an overall harsher environment. We found that relative seasonal growth had no effect on individual longevity or on juvenile and adult annual survival. For yearlings, the effect of relative seasonal growth on survival depended on the location: yearlings with high relative seasonal growth had lower survival if located up-valley, and higher survival if located down-valley. In conclusion, juveniles and adults do not appear to have detectable costs of rapid growth, although there are costs to yearling survival depending on environmental conditions. Substantial structural growth occurs when marmots are yearlings and our results are likely driven by the high conflicting demands of somatic growth versus maintenance at this stage. Thus, the costs of rapid growth are age and site dependent and may be seen in the short term for species facing temporal constraints on growth. Abstract : Compensatory growth allows individuals to recover from adverse conditions early in life but often at a cost. How and when these costs play out during the life histories of individuals in the wild is not well understood. Using generalized linear and mixed-effect modeling, we demonstrate that survival costs of accelerated growth in yellow-bellied marmots vary by age and location. Costs are most evident in yearling marmots and are paid early in life.